The impact of standard value added tax on economic growth in CEE-5 countries: econometric analysis and simulations - Simionescu, Mihaela; Albu, Lucian-Liviu (Technological and Economic Development of Economy, 2016)
The value added tax (VAT), as an instrument of fiscal policy, might have an important role on economic growth. This study analyzes the impact of standard VAT rate on economic growth in five Central and Eastern European countries (CEE-5) (Bulgaria, Czech Republic, Hungary, Poland and Romania). Different types of panel data models (random effect model, dynamic panel and panel vector-autoregression) over 1995–2015 indicated a positive influence of VAT rate on economic growth. There is a bilateral Granger causality between economic growth and VAT rate. The Bayesian linear models indicate a positive effect of VAT rate on GDP rate only for Hungary. On short-run, the other countries register lower GDP rates when VAT rates increase. Some simulations of economic growth for 2016 and 2018 were made for each CEE-5 country under different assumptions regarding VAT rate values. First published online: 23 Nov 2016